BERMAIN KONSTRUKTIF UNTUK MENINGKATKAN KEMAMPUAN BERBICARA PADA ANAK USIA 4-5 TAHUN - Lestiawati I Made (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Constructive play is an imaginative and fun game. This is important for children's development, one of which is the ability to speak as a communication tool for children to express all ideas and feelings when playing constructively, children can explore with their imaginations, learn to find and pour new ideas, do problem-solving and recognize rules. The research method used is descriptive qualitative research. The purpose of this study was to see the meaning and benefits of constructive play. Constructive play activities emphasize the nature of the building and creating something that can stimulate children's speaking skills. Qualitative data analysis using the model from Miles and Huberman through triangulation: (1) data reduction, (2) data display, (3) verification, through observation, interviews and documentation during the action. The results showed that constructive play based on peer groups can develop children's speaking skills. Through the experience of playing, creating and interacting with peer groups, children can improve all aspects of their speaking ability.